2021
DOI: 10.3390/biology10010030
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Extracts from Tiger Milk Mushroom Lignosus rhinocerus Against Glutamate-Induced Toxicity in HT22 Hippocampal Neuronal Cells and Neurodegenerative Diseases in Caenorhabditis elegans

Abstract: Despite the Tiger Milk Mushroom Lignosus rhinocerus (LR) having been used as a traditional medicine, little is known about the neuroprotective effects of LR extracts. This study aims to investigate the neuroprotective effect of three extracts of LR against glutamate-induced oxidative stress in mouse hippocampal (HT22) cells as well as to determine their effect in Caenorhabditis elegans. In vitro, we assessed the toxicity of three LR extracts (ethanol extract (LRE), cold-water extract (LRC) and hot-water extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 64 publications
(41 reference statements)
1
11
0
Order By: Relevance
“…Our study confirms a previous report showing that an ethanol extract of LR (LRE) exerted the highest antioxidant activity in vitro via DPPH and ABTS free radical scavenging capacity [15,42]. The bioactive compounds of LRE identified by GLC-MS, including phenol, oleic acid, linoleic acid, and ethyl ester, as shown in Table 2, have been reported to have antioxidant properties [27,43,44]. These phytochemical constituents are similar to the LC-MS results from our research group [16] and the GLC-MS data from other findings [12,13,45].…”
Section: Discussionsupporting
confidence: 90%
“…Our study confirms a previous report showing that an ethanol extract of LR (LRE) exerted the highest antioxidant activity in vitro via DPPH and ABTS free radical scavenging capacity [15,42]. The bioactive compounds of LRE identified by GLC-MS, including phenol, oleic acid, linoleic acid, and ethyl ester, as shown in Table 2, have been reported to have antioxidant properties [27,43,44]. These phytochemical constituents are similar to the LC-MS results from our research group [16] and the GLC-MS data from other findings [12,13,45].…”
Section: Discussionsupporting
confidence: 90%
“…Although glutamate plays an essential role in neurotransmitters, a high glutamate level in the brain shows a risk of NDDs [16,28]. Several edible mushroom-derived products have been reported to attenuate glutamate-induced neurotoxicity [29][30][31]. Our study found that APE and APH could decrease the toxicity of glutamate on HT-22 cells.…”
Section: Discussionmentioning
confidence: 47%
“…Herein, we demonstrated that exposure to high-concentration of glutamate could exert antioxidant mechanisms by decreasing antioxidant enzymes and increasing oxidative stress, leading to neuronal damage [31,38]. In contrast, the treatment of NAC could attenuate the effects of glutamate.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations